KARAKTERISTIK FUNGSIONAL POLISAKARIDA PEMBENTUK GEL DAUN CINCAU HIJAU (Premna Oblongifolia Merr.) - Samsu Udayana Nurdin; Suharyono A.S Suharyono A.S; Samsul Rizal (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2008)
The effect of citric acid concentration on functional characteristics of polysaccharide forming gel (PFG) of green cincau leaves (Premna Oblongifolia Merr.) were evaluated. PFG of green cincau leaves were extracted through the use of citric acid (0,0%, 0,1%, 0,2%, 0,3%, 0,4%, and 0,5% w/v) solution, precipitated using ethanol, and followed by drying of the extracts. The results showed that increasing of citric acid levels reduced the viscosity, water holding capacity, and bulking capacity of the PFGs. Oil holding capacity and water solubility were not affected by citric acid addition. The addition of 0.0% citric acid produced the highest viscosity, water holding capacity, and bulking capacity suggesting possible uses of the extract as dietary fibre with good laxative effect. Key Words: Green cincau leaves, functional characteristic, dietary fibre.